The Design of Patterns Inspired by Gunungan Wayang With Unused Jeans To Stool Product: PERANCANGAN MOTIF INSPIRASI GUNUNGAN WAYANG MENGGUNAKAN CELANA JEANS BEKAS UNTUK PRODUK STOOL - Salsabila Alfianti (University of Nahdlatul Ulama Pasuruan, 2023)
This design was made to response the problem of unused jeans in the neighborhood. Jeans have become one of the types of clothing that is common in the public but the lack of control in use that make new environmental problems. It is necessary to design with unused jeans material into stools with batik writing, bleaching, engraving and sewing techniques that can communicate the concepts. The concept of Gunungan was to introduce one of the cultures to the community, as well as the use of unused jeans as an alternative materials as the environmental friendly raw materials. The method that being used in this design process is the theory of the creation of SP. Gustami which about the stages of exploration, design and production. Exploration stage is to find data and explore concepts and techniques. The design stage is the form of making stool product designs and patterns with aspects as a consideration. The last stage is the production process as realization process from designed in stool products. The results in this design process are 8 designs with 3 products realized into stool products with the Gunungan concept as the patterns which appeared with the batik writing technique.